RIGHTS AND DUTIES OF FOREIGN SHIPS TO INDONESIAN ARCHIPELAGIC SEA LANES PASSAGE - St Fatmawati L; Rifkah Anniza Rahman; Nadya Khaeriyah Yusran (Fakultas Hukum, Universitas Diponegoro, 2023)
Every country has the right to sail in its territorial sea, exclusive economic zone, high seas, and other countries' territorial seas. However, when crossing the territorial areas of other countries, foreign ships must obey and follow all regulations in that area to go through. This research uses a normative legal research typology method which includes field research focusing on positive legal norms in the form of laws and regulations and literature research to determine the regulation of the rights and obligations of foreign ships to cross the Indonesian archipelagic sea lanes. The results of this study indicate that the rights and obligations of foreign ships to cross the Indonesian archipelagic sea lanes have been regulated in several regulations, both national regulations and international regulations, but in practice, the high intensity of foreign ships passing through ALKI causes many problems. The problems that arise because of these passages have not all been resolved by existing laws and regulations, so these regulations are considered ineffective and insufficient in overcoming the problems of the Indonesian archipelagic sea lanes.